2020
DOI: 10.1002/stc.2600
|View full text |Cite
|
Sign up to set email alerts
|

Model updating‐based automated damage detection of concrete‐encased composite column‐beam connections

Abstract: Summary This paper presents a comparative study about the numerical and experimental system identification and model updating‐based automated damage detection of concrete‐encased composite column‐beam connections. Four different column‐beam connection types named as CBC#A, CBC#B, CBC#C, and CBC#D were considered without any changes in geometrical configuration. Numerical and experimental dynamic characteristics were extracted by initial finite element analysis and nondestructive experimental measurements for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…When the damage in a concrete member is not obvious or difficult to quantify (e.g., some hidden defects after shock events), frequencybased FE model updating is a possible approach to localizing the damage. To model the damage in concrete-encased composite column-beam connections after an earthquake, Nasery et al [50] conducted a cyclic loading test on four samples with different connections (as shown in Figure 6a). Concrete failure and some welding damages can be observed after the loading test (see Figure 6b).…”
Section: Reviewmentioning
confidence: 99%
“…When the damage in a concrete member is not obvious or difficult to quantify (e.g., some hidden defects after shock events), frequencybased FE model updating is a possible approach to localizing the damage. To model the damage in concrete-encased composite column-beam connections after an earthquake, Nasery et al [50] conducted a cyclic loading test on four samples with different connections (as shown in Figure 6a). Concrete failure and some welding damages can be observed after the loading test (see Figure 6b).…”
Section: Reviewmentioning
confidence: 99%
“…This method involves manipulating the natural frequency of the structure and modeling the crack using a torsional spring, allowing for precise crack assessment. Nasery et al [7] proposed an approach for automated damage detection in concrete-encased composite column-beam connections using model updating techniques. Their findings demonstrated that their proposed method identified the location and severity of the damage.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al [ 13 ] proposed a type of prefabricated SRC columns reinforced by angle steel and analyzed the influences of steel ratios, stirrup spacings and prefabrication details on the axial compressive behavior and seismic behavior. Nasery et al [ 14–17 ] conducted a series of investigations of concrete encased composite column‐beam connections. It was first ever research to investigate the changes in dynamic characteristic of the encased steel profile column‐beam connections before and after lateral cyclic loading test by adopting preambient vibration measurements.…”
Section: Introductionmentioning
confidence: 99%